Analisis Wacana Kritis Teks Berita Kasus Terbongkarnya Perlakuan Istimewa terhadap Terpidana Suap Arthalyta Suryani pada Media Online - Ellyawati, Hetty Catur (Jurnal The Messenger, 2011)
Every choice of meaning is ideologically motivated. Ideology is most effective when its working is least visible. Interpreting ideology in a text can be seen from the choice of vocabulary and its grammatical construction. To analyze it we need to interpret not just the text but also the relationship between text, and its social condition. According to Fairclough, they can be grouped in three steps, those are description, interpretation and explanation. The stage of description is concerned with formal properties of the text, the interpretation is concerned with the relationship between text and its interactions, the explanation is concerned with the relationship between interpretation and social context. This research aims to analysis the coverage about the revealed case of preferential treatment of Arthalyta Suryani, a convicted bribe, at Pondok Bambu detention written by two online media these are detikNews.com and kompas.com by analyzing their appraisal system and their intertextuality. From the data analysis, ideology of the two media about this case can be seen. The data is taken from the news posted on January the tenth to twelfth 2010.  The methods used to analyze the data are referential method, substitusional method and abductive inference method.     Referential method is to analyze appraisal system and discursivity intertextuality of the text. In order to make the analysis of appraisal system valid, the substitusional method is needed. Then abductive inference method is needed to analyze manifest intertextuality of the text. From the analysis of the data, it can be concluded that every media has its own way to state its ideology. The ideology has closed relation with target market that is the reader. DetikNews.com is strightforward and short news, with incisive vocabulary choices, they are related to news item genre that detikNews.com has, but this media is lack of intertextuality. It makes the news superficial. On the other way, kompas.com has a deep coverage and strong intertextuality, it is suitable for someone who wants comprehensive information.